HPV vaccination, information sources, and acculturation among Chinese college students aged 18–26 in the United States. Issue 2 (21st September 2021) - Tung, Wei‐Chen; Lin, Yuting; Chao, Hannah W.; Chen, Yinghan
Abstract: Human papillomavirus (HPV) vaccination behaviors among Chinese college students (CCS) in the United States are affected by social determinants of health. Using a self‐report questionnaire and a snowball sampling technique, this cross‐sectional study investigated (a) HPV vaccination practices; (b) primary social networking platforms and preferred means of receiving HPV information; and (c) the influence of acculturation on HPV vaccination, HPV information sources, and social networking use among 213 CCS aged 18–26 in the United States. About half (50.7%) had received one to three doses of an HPV vaccine, and 91.7% had received their first dose. The most popular social networking platforms were WeChat (69.5%), Instagram (58.7%), text messaging (55.4%), and Facebook (47.4%). Preferred means of receiving future HPV information included the internet, online social networking, and health professionals. Participants with high Asian identification (AI) were less likely to receive the HPV vaccine than those with high Western identification. Participants with high AI were more likely to use WeChat for their social networking but less likely to use US‐based social media platforms. Acculturation, preferred social networking platforms, and sources and communication of HPV (i.e., health professionals, family members, schoolteachers, friends) influenced participants' HPV vaccination. To promote equity of access to health messages and increase HPV vaccination, future efforts should pay attention to CCS with high AI and incorporate their cultural beliefs and practices. Given that nonprofessionals (e.g., family, friends) were influential factors in HPV vaccination, it is critical to tailor interventions for CCS to the recipients and their social circles.